Platform of Ideological and Political Education in Colleges and Universities Based on Machine Learning Algorithm - Siyuan Hu, Jingsheng Wang (Design Engineering, 2021)
The survey shows that network teaching in Ideological and Political (I&P) theory course is generally accepted by learners, which is a completely positive practice. Network teaching platform can be constructed from three aspects: system design, element rules and mechanism operation. Under the premise of active machine learning field, taking the online I&P education teaching system as an example, this paper studies the general application of machine learning in the I&P education network teaching system. This paper describes the I&P education model, which is based on the recommendation system of students’ preferences and includes three machine learning models. This paper realizes the feature extraction and classification of users and projects, and finally completes a more comprehensive machine learning application system of personalized project recommendation for users. This paper further explores the application of a personalized and scalable machine learning in Online I&P education.